Public awareness towards instruments for river bank conservation - Zehegkiel, Piree (Universiti Malaysia Sarawak (UNIMAS), 2006)
As elsewhere in the world, rivers played an important role in economic, social, cultural and religious life of the people in Malaysia, particularly in Sarawak. It is known that a river is the lifeline of a community. In fact, riverine communities have a distinct culture with their own tradition, practices and beliefs. These communities even built their houses either at the edge of the river or on the adjacent areas. The ultimate battle for the health of a river, is won on land. If the land within a watershed is not treated properly, the river will be impacted, perhap even to the point where it is no longer suitable for people to survive. Although all land within a watershed is important, the land directly adjacent to a river or stream is particularly critical to its health. A study has been carried out at Sg. Sarawak Kiri from Batu Kitang to Kpg. Semadang which involved six (6) kampungs. From a study carried out, it was found out that although there is a broad consistency about general widths recommended and types of developments or activities allowed for riparian areas due to differences depending on the aim sought, location and the regulatory. This is because of lack of awareness among the respondents in protecting the river. One of the most important aspects of river conservation, particularly in zoning method, is a links that the activities forge between people. A group that has a share goal for the river brings together individuals from a wide range of backgrounds, interests and areas of expertise to ensure they achieve the goal.